APPLICATION OF THE NUMBERED HEADS TOGETHER LEARNING MODEL WITH VIRTUAL LABORATORY SUPPORT ON WRITTEN COMMUNICATION - Joko Wahyu Setyono; Azhar Azhar; Imam Mahadi (SPEKTRA: Jurnal Kajian Pendidikan Sains, 2024)
Science education is now adapting to 21st-century skills. One rarely implemented stage is the ability of students to communicate in writing because the lack of attention given by teachers. This study addresses the issue of how the implementation, whether there are differences, and the improvement of cooperative learning model type NHT assisted by virtual laboratories affect written communication on the topic of simple machines for eighth-grade junior high school students. This research aimed to investigate the implementation of the NHT learning model supported by virtual laboratory tools in improving written communication skills. The research method used is descriptive quantitative research, employing a quasi-experimental design, specifically the matching only posttest group design. The study was conducted at Class VIII of State Junior High School 5 Tandun. The sample consists of two eighth-grade classes: Class VIII-1 with 23 students as the experimental group and Class VIII-2 with 23 students as the control group.. The results of the study revealed that the overall average score for all aspects in the NHT class with virtual laboratory support was 88%, indicating a "very good" performance category. On the other hand, the average score for all aspects in the scientific class was 82%, falling into the "good" category. The t-test results indicated a significance value (2-tailed) of 0.037, indicating a significant difference in the written communication abilities of students between the class using the NHT learning model with virtual laboratory support and the scientific class, specifically in the context of simple machines.